A novel approach for grafting of β-cyclodextrin onto wool via laccase/TEMPO oxidation. (20th November 2016) - Yu, Yuanyuan; Wang, Qiang; Yuan, Jiugang; Fan, Xuerong; Wang, Ping
Highlights: Aldehyde groups were introduced in β-cyclodextrin by laccase/TEMPO oxidation. Schiff base between aldehydes in β-cyclodextrin and amino groups in wool was formed. β-cyclodextrin-grafted wool was prepared by laccase/TEMPO treatment. Abstract: This study demonstrated a new enzymatic methodology to graft β-cyclodextrin onto wool. The primary hydroxyl groups in β-cyclodextrin were oxidized to aldehyde groups using laccase/2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO), which reacted with the amino groups of wool to form Schiff bases. The effects of treatment conditions (treatment temperature, laccase dosage, TEMPO dosage, treatment time) on the aldehyde and carboxyl contents in β-cyclodextrin were studied. FTIR spectrum of oxidized β-cyclodextrin showed the presence of aldehyde and carboxyl groups. Results of MALDI-TOF mass spectroscopy confirmed the coupling of β-cyclodextrin to tyrosine, which was used as a model compound for wool. ATR-FTIR spectroscopy of the grafted wool confirmed the presence of β-cyclodextrin in grafted wool and the formation of a Schiff base between β-cyclodextrin and wool.